Financial depth or breadth - JOMBO, Wytone Yohane (KDI School, 2015)
The standardized beta coefficients are utilized in the environment of Pooled OLS, Fixed Effects and Two-Stage Least Squares estimators to determine that the exposure of a larger portion of adult population to financial services has a greater impact on economic growth than the sheer size of the financial sector. The paper, nevertheless, finds both financial depth and financial breadth indicators statistically and economically significant. The results are consistent and robust even when the estimation is conducted in stricter conditions and with competing models. While previous research work in this area has only focused on investigating whether financial development has an impact on growth or not, this paper nobly contributes to the existing literature by establishing that in the class of financial development indicators, financial breadth indicators are stronger in explaining economic growth in SSA than financial depth indicators.
Thesis(Master) --KDI School:Master of Development Policy,2015